African and Borneo beads : comparative analysis of semantic and semiotics - Ehimen, Osakue Emmanuel (Universiti Malaysia Sarawak (UNIMAS), 2008)
The purpose of this research is to present a comprehensive analysis of African and Borneo Beads, and unveil the various messages and roles beads played in these two communities. In understanding the roles of African and Borneo beads, relevant theories have been examined to outline the symbolic classification system observed to be prevalent between these two cultures. Studies of beads sign as cultural phenomena deals closely with social functions which review customs and structures through semantic and semiotic analysis of visual concept. There are various reasons why certain elements like forms, materials, colours and ornaments are used in certain beads in Africa and Borneo. The semantic interpretations of these elements as well as the semiotic analysis of beads symbols explain the significance, communication, expression and representations of beads in Africa and Borneo.